A Theoretical Framework For The Evaluation Of Virtual Reality Technologies Prior To Use: A Biological Evolutionary Approach Based On A Modified Media Naturalness Theory - Yumurtacı, Onur (The Turkish Online Journal of Design Art and Communication, 2016)
The rapid development of information and communication technologies has opened a whole new realm of applications for these technologies. One such application is the development of virtual reality, which aspires to immerse the user within the system such that they feel more “present” within the portrayed virtual plane of existence than within their true reality. Many studies have developed a variety of approaches and methods on measuring immersion and presence in these systems, yet few have addressed the underlying technology for what it really is – namely communication technology – and evaluated the technology’s potential for immersion and presence before exposing the user to the virtual experience. Part of the issue lies in the difficulty in quantifying arguably subjective experiences such as immersion and presence. This study examines the existing literature on the definition and evaluation of immersion, presence, and virtual reality technologies, and aims to provide a theoretical framework through which virtual reality technology may be evaluated based on the human biological apparatus it appeals to. The framework is constructed on a modified version of the Media Naturalness Theory, which was selected as a basis due to the evolutionary support it provides in explaining our communication preferences. The framework may then be utilized to analyze prospective technologies for their potential to provide immersive experiences and incite presence in the users before any exposure or use has taken place, possibly providing further validity to any findings of post-exposure studies (such as with questionnaires so ubiquitous in the literature of the field).
Keywords: virtual reality; technology; immersion; presence; Media Naturalness Theory